(untitled) - Manning, Erin (New York, 2012)
Taking great "people pictures" isn't a matter of luck. The secret is in observing your subjects and connecting with them, and then using your camera to its best advantage. This new edition uses full-color photos to demonstrate how to work with lighting, location, angle, composition, physical characteristics, and environment in either portrait or candid situations. Professional photographer and veteran author Erin Manning offers invaluable advice for handling the unique challenges of photographing babies, large and small groups, and action.
Keywords: Chụp ảnh chân dung,Portrait photography; Kỹ thuật,Technique